Ecosystems say good management pays off. Issue 1 (12th October 2018) - Fulton, Elizabeth A.; Punt, André E.; Dichmont, Catherine M.; Harvey, Chris J.; Gorton, Rebecca
Abstract: Understanding the strengths and weaknesses of alternative assessment methods, harvest strategies and management approaches are an important part of operationalizing single‐species and ecosystem‐based fisheries management. Simulations run using two variants of a whole‐of‐ecosystem model for the Southern and Eastern Scalefish and Shark Fishery (SESSF) area shows that (a) data‐rich assessments outperform data‐poor assessments for target species and that this performance is reflected in the values of many system‐level ecosystem indicators; (b) ecosystem and multispecies management outperforms single‐species management applied over the same domain; (c) investment in robust science‐based fisheries management pays dividends even when there are multiple jurisdictions, some of which are not implementing effective management; and (d) that multispecies yield‐oriented strategies can deliver higher total catches without a notable decline in overall system performance, although the resulting system structure is different to that obtained with other forms of ecosystem‐based management.